Right ventricular outflow tract morphology and its clinical significance for invasive procedures - Marcin Jakiel; Rafał Jakiel; Jakub Batko; Edyta Dyngosz; Maria Kurek; Karolina Gutkowska; Jakub Hołda; Filip Bolechała; Marcin Strona; Mateusz K. Hołda (Scientific Reports)
Abstract We aimed to evaluate in detail the right ventricular outflow tract (RVOT) morphology to enhance clinical procedures performed within this area. Two hundred twenty autopsied adult human hearts (37.2% females, 47.6 ± 18.0 years old) without macrostructural cardiac abnormalities were examined. The RVOT was macroscopically and morphometrically evaluated. The RVOT has a truncated cone shape with the elliptical RVOT base being significantly larger than its distal boundary (pulmonary root basal ring) (mean perimeter: 126.6 ± 27.7 vs. 73.2 ± 11.6 mm, p < 0.001). The right RVOT wall is the highest (30.5 ± 6.1 mm), followed by the anterior (29.4 ± 7.3 mm), left (27.3 ± 6.4 mm), and posterior (26.9 ± 6.5 mm). The RVOT may be divided into the free-standing thin-walled subpulmonary infundibulum and the septal component, which constitutes a significant portion of the RVOT posterior wall (37.3 ± 13.8%). The RVOT wall thickness demonstrated significant differences among the respective RVOT walls and across the RVOT levels. The length of the supraventricular crest is 29.1 ± 6.9 mm, and it narrows along its course (thickness at origin: 12.26 ± 2.9 mm vs. at termination: 9.2 ± 1.9 mm, p < 0.001). The length of the septoparietal band is 16.6 ± 3.9 mm, and its thickness remains relatively constant along its entire length (at origin: 6.9 ± 1.6 mm, at termination: 7.2 ± 2.4 mm, p = 0.124). Endocardial roughness of the RVOT, such as trabeculations, recesses, or muscular bridges, are present in all hearts within the subpulmonary infundibulum and in only 8.2% of the septal component. No significant differences between sexes were found in any of the measured RVOT parameters. In conclusion, this study provides a detailed definition, along with anatomical and structural analysis of the RVOT, highlighting its complex morphology and its significant role in cardiac functionality and clinical interventions.